1992
DOI: 10.1182/blood.v79.6.1441.bloodjournal7961441
|View full text |Cite
|
Sign up to set email alerts
|

Different specificities of platelet-associated and plasma autoantibodies to platelet GPIIb-IIIa in patients with chronic immune thrombocytopenic purpura

Abstract: Chronic immune thrombocytopenic purpura (ITP) is an autoimmune disorder due to antiplatelet autoantibodies, many of which are directed against platelet membrane glycoprotein (GP) IIb-IIIa or GPIb-IX. In a recent study, we described plasma autoantibodies from 13 selected ITP patients, which required the presence of the putative GPIIIa cytoplasmic region for antibody binding. Since this region may not be available for antibody binding under physiologic conditions, we evaluated the frequency of binding to this or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…The data using P-GP-ELISA suggest that free Ab differ from Ab bound to the Plt in specificity and/or affinity, i.e. plasma Ab are not just the unbound remainder of Plt-associated Ab, which is consistent with previous reports (McMillan et al, 1987;Fujisawa et al, 1992). Therefore it has to be emphasized that the importance of circulating Ab in ITP patients should be interpreted very cautiously.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The data using P-GP-ELISA suggest that free Ab differ from Ab bound to the Plt in specificity and/or affinity, i.e. plasma Ab are not just the unbound remainder of Plt-associated Ab, which is consistent with previous reports (McMillan et al, 1987;Fujisawa et al, 1992). Therefore it has to be emphasized that the importance of circulating Ab in ITP patients should be interpreted very cautiously.…”
Section: Discussionsupporting
confidence: 87%
“…In an intact Plt, epitopes on the cytoplasmic domain of membrane proteins are inaccessible. Nevertheless, such epitopes may be recognized by plasma Ab (Fujisawa et al, 1992), possibly provoked as a secondary phenomenon of Plt destruction. Since in P-GP-ELISA, Pltglycoprotein-binding Ab were eluted from intact Plt, Ab directed against cytoplasmic domains should not be present.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the view that measurement of plasma autoantibodies against platelet glycoproteins is inferior to methods for platelet-associated autoantibodies in AITP. In addition, it has been shown that the specificity of plasma antibodies may differ from that of antibodies bound to platelets and that some of them may bind to cytoplasmic epitopes (Fujisawa et al, 1991(Fujisawa et al, , 1992. This suggests that measurement of plasma autoantibodies may be misleading in the evaluation of AITP.…”
Section: Discussionmentioning
confidence: 99%
“…These autoantibodies are detected in the majority of AITP patients as platelet-associated antibodies, whereas plasma autoantibodies are noted in a smaller number of patients Berchtold & Wenger, 1993). This difference may be important, since the specificity of antibodies bound to the platelet may differ from that of plasma antibodies and some of the latter are directed against antigens on the cytoplasmic portion of GPIIIa (Fujisawa et al, 1991(Fujisawa et al, , 1992. been developed Kiefel et al, 1987).…”
mentioning
confidence: 99%
“…In comparison, chronic idiopathic thrombocytopenic purpura (ITP) is an autoimmune disease caused by circulating antibodies that react with the target antigen on the platelet membrane, with the consequence that the platelets are recognized and eliminated by the host's immune system. Specific tests that characterize the target of such anti-platelet antibodies have shown that many are directed against surface glycoproteins such as GP IIb-IIIa (Woods et al, 1984b;Fujisawa et al, 1992) and GP Ib-IX (Woods et al, 1984a;Kiefel et al, 1991). Other glycoproteins implicated in isolated cases include GP Ia-IIa (Deckmyn et al, 1990(Deckmyn et al, , 1994, GP IV (Beer et al, 1993) and GP V (Mayer & Beardsley, 1996).…”
mentioning
confidence: 99%